2006
DOI: 10.1017/s0305000905007154
|View full text |Cite
|
Sign up to set email alerts
|

Word learning deficit among Chinese dyslexic children

Abstract: A B S T R A C TThe present study examined word learning difficulties in Chinese dyslexic children, readers of a nonalphabetic script. A total of 105 Hong Kong Chinese children were recruited and divided into three groups : Dyslexic (mean age 8; 8), CA control (mean age 8;9), and RL control (mean age 6; 11). They were given a word learning task and a familiar word writing task. It was found that the Dyslexic group performed less well than the RL group in learning irregular words over trials but not the regular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…There are even fewer studies that have attempted to show the characteristics of reading comprehension and its related skills in Chinese dyslexic children, as distinct from that of typically developing children. More recently, Ho and her colleagues have showed that Chinese dyslexic children performed less well than average readers matched on reading level in learning irregular words over trials but not the regular ones (Ho, Chan, Tsang, Lee, & Chung 2006); and most of them were found performing poorer than expected of their age in rapid naming and orthographic processing tasks (Ho, Chan, Lee, Tsang, & Luan 2004). Further investigation into text comprehension and its associated cognitive and reading-related skills between dyslexic and typically developing children should be revealing.…”
Section: Introductionmentioning
confidence: 99%
“…There are even fewer studies that have attempted to show the characteristics of reading comprehension and its related skills in Chinese dyslexic children, as distinct from that of typically developing children. More recently, Ho and her colleagues have showed that Chinese dyslexic children performed less well than average readers matched on reading level in learning irregular words over trials but not the regular ones (Ho, Chan, Tsang, Lee, & Chung 2006); and most of them were found performing poorer than expected of their age in rapid naming and orthographic processing tasks (Ho, Chan, Lee, Tsang, & Luan 2004). Further investigation into text comprehension and its associated cognitive and reading-related skills between dyslexic and typically developing children should be revealing.…”
Section: Introductionmentioning
confidence: 99%
“…Successful word recognition is therefore inevitably reliant on the ability to form correct association between visual word forms and their corresponding pronunciations (Ho, Chan, Tsang, Lee, & Chung, 2006;Li et al, 2009), in particular for beginning readers who are less likely to optimally utilize phonological cues to assist their word acquisitions. This may have contributed to the specific role of working memory for binding between visual and auditory-verbal modalities in predicting early progress in learning to read that was observed in this study.…”
Section: Discussionmentioning
confidence: 99%